Relating Divergent Worlds: Mines, Aquifers and Sacred Mountains in Peru - Li, Fabiana (Anthropologica, 2013)
This article examines a conflict over the expansion, into Cerro Quilish (Mount Quilish), of the Yanacocha gold mine, in Northern Peru. In campaigns against the mine, Cerro Quilish was an aquifer (a store of life-sustaining water) and an Apu (usually translated from Quechua as "sacred mountain"). Neither the product of ancestral tradition nor the invention of antimining activists, Cerro Quilish came into being through knowledge encounters that brought together actors with diverse interests, although at times a single entity—water—became the central focus of debate, obscuring other realities. Drawing on science and technology studies literature, I examine the practices that bring entities into being and argue that contem porary conflicts involve an ongoing process of contestation over socionatural worlds.